Leucine supplementation enhances integrative myofibrillar protein synthesis in free-living older men consuming lower- and higher-protein diets: a parallel-group crossover study. Issue 6 (9th November 2016) - Murphy, Caoileann H; Saddler, Nelson I; Devries, Michaela C; McGlory, Chris; Baker, Steven K; Phillips, Stuart M
ABSTRACT: Background: Leucine co-ingestion with lower-protein (LP)–containing meals may overcome the blunted muscle protein synthetic response to food intake in the elderly but may be effective only in individuals who consume LP diets. Objective: We examined the impact of leucine co-ingestion with mixed macronutrient meals on integrated 3-d rates of myofibrillar protein synthesis (MyoPS) in free-living older men who consumed higher protein (HP) (1.2 g · kg –1 · d –1 ) or LP (0.8 g · kg –1 · d –1 ) in rested and resistance exercise (REX) conditions. Design: In a crossover design, 20 healthy older men [aged 65–85 y] were randomly assigned to receive LP or HP diets while ingesting a placebo (days 0–2) and Leu supplement (5 g leucine/meal; days 3–5) with their 3 main daily meals. A bout of unilateral REX was performed during the placebo and Leu treatments. Ingested 2 H2 O and skeletal muscle biopsies were used to measure the 3-d integrated rate of MyoPS during the placebo and Leu treatments in the rested and REX legs. Results: Leucinemia was higher with Leu treatment than with placebo treatment ( P < 0.001). MyoPS was similar in LP and HP during both treatments ( P = 0.39) but was higher with Leu treatment than with placebo treatment in the rested (pooled mean ± SD: Leu, 1.57% ± 0.11%/d; placebo, 1.48% ± 0.08%/d; main effect of treatment: P < 0.001) and REX (pooled mean: Leu, 1.87% ± 0.09%/d; placebo, 1.71 ± 0.10%/d; main effect of treatment: P < 0.001) legs. Conclusions: Leu co-ingestion with daily meals enhances integrated MyoPS in free-living older men in rested and REX conditions and is equally effective in older men who consume daily protein intakes greater than or equal to the RDA. This trial was registered at clinicaltrials.gov as NCT02371278.